2017
DOI: 10.1097/01.npr.0000521997.84052.ef
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning Florida NPs to opioid prescribing

Abstract: Prior to statutory changes in prescriptive authority for controlled substances, this study examined the knowledge gaps and prescribing limitations of Florida advanced registered nurse practitioners regarding opioids. Study results revealed statistically significant knowledge gaps in the areas of federal and state guidelines; opioid classes and proper doses; risk assessment skills; monitoring of treatment; and confidence in dealing with challenges of opioid prescribing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Six of nine articles identified professional education as either a barrier or a facilitator for NPs' management of chronic pain (Craig-Rodriguez et al, 2017; Franklin et al, 2013; Mazurenko et al, 2020; Nikpour et al, 2021; Spitz et al, 2011; St Marie, 2016). As barriers to opioid prescription for older adults, 77% of NPs and physicians in one study identified fear of causing harm from adverse effects, and 35% identified insufficient pain management education (Spitz et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six of nine articles identified professional education as either a barrier or a facilitator for NPs' management of chronic pain (Craig-Rodriguez et al, 2017; Franklin et al, 2013; Mazurenko et al, 2020; Nikpour et al, 2021; Spitz et al, 2011; St Marie, 2016). As barriers to opioid prescription for older adults, 77% of NPs and physicians in one study identified fear of causing harm from adverse effects, and 35% identified insufficient pain management education (Spitz et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Four of nine articles reported that NPs' restricted prescriptive authority was a barrier to managing opioid issues (Craig-Rodriguez et al, 2017; Mack, 2018; Nikpour et al, 2021; Spitz et al, 2011). Restricted authority in Florida was initially a barrier for APRNs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 At the time, Florida was still trying to repair its reputation as the "epicenter of prescription drug diversion" in the US. 5,6 Just 6 years earlier, the DEA had reported that Florida physicians were dispensing fi ve times more oxycodone than the national average, resulting in a massive increase in deaths from opioid misuse. 5,6 Subsequent increased regulation of pain clinics and standardization of physician prescribing guidelines and monitoring dramatically decreased overdose deaths in the state.…”
Section: ■ Backgroundmentioning
confidence: 99%